About the relationship of rosacea-like dermatitis - Andrey L. Bakulev; Maria V. Bakuleva (Vestnik Dermatologii i Venerologii, 2023)
The literature review is devoted to the problem of rosacea-like dermatitis developing in patients with rosacea against the background of irrational uncontrolled use of topical glucocorticosteroids or cosmetics. The clinical picture of the combined pathology consists of symptoms characteristic of both diseases, which makes diagnosis difficult.